THE CORRELATION BETWEEN ATTITUDE TOWARDS CERVICITIS PREVENTION AND SCREENING CHECKUP - Freya Nazera Iskandar; Dewi Puspitaningrum; Lia Mulyanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Cervicitis is an infection that is caused by little injury of former childbirth or sexual intercourse. In several venereal diseases like gonorrhea, syphilis, ulcers mole, granuloma inguinal and tuberculosis are found inflammation cervix.Cases of cervicitis according to data result of the number of graphs of sexually transmitted infections patient who got treatment at semarang city hospital from last recap year 2010 is in the first rank as many as 5111 people. Public Health Center of Lebdosari Semarang City has the highest case of cervicitis, in 2012 the case cervicitis 356 people (66.9%), while in 2013 as many as 129 people (24.24%). Objective: To prevent cervicitis from the beginning cases researched to know the correlation between women’s attitude (age 20 – 35 years) towards cervicitis prevention behavior and screening check-up in Kalibanteng Kulon district Lebdosari Semarang. Method: This research is analytic research with cross sectional approach. The population is 532 fertile women with sample 84 respondents in Kalibanteng Kulon district Lebdosari Semarang of citizens group number 2. 3 and 4 of the interview questionnaire. Probability sampling is used in this research with simple random sampling by lottery technique sampling. Data analysis uses univariate and bivariate. Result:Based on the Chi Square test gets score X2 19.931 with p value (0.000) < α (0.05). It means there are relations between women’s attitude to cervicitis prevention behavior with screening checkup in Kalibanteng Kulon district Lebdoasari Semarang. Conclusion: There are relations between fertile women attitude (age 20 – 35 years) to cervicitis prevention behavior with screening check-up in Kalibanteng Kulon District Lebdosari Semarang.